ANALYSIS ON THE DOCTRINE OF LIMITED LIABILITY UNDER COMPANY LAW AND SHARĪ‘AH - Zuhairah Ariff Abd Ghadas; Hartinie Abd Aziz, (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2019)
Under company law, the doctrine of limited liability is applied to promote economic development via a legal entity. The main advantage of a limited liability is that it enables business owners to reduce and transfer the risks in business to their company. However, the application of limited liability is often criticized for causing unfairness to creditors. Under English common law, which is the basis of Malaysian company law, a body corporate is recognized as a legal person distinct from the owners. The metaphor of corporate personality is used to justify the attributes of a company as a legal person and its ability to limit liability of its members. However, such principle is not found in Sharī‘ah business entities because under Islamic law, a business entity is not separated from the owner and as such, the owner cannot totally transfer the business risks to the business entity. A doctrinal analysis was carried out to analyze the application of the doctrine of limited liability under Malaysian company law and to compare it with the Sharī‘ah principles dealing with limited liability. The purpose of this paper is to indicate whether the limited liability regime, which is conferred to conventional companies in Malaysia, could be directly applied to Malaysian companies which are carrying out Sharī‘ah-compliant businesses.